El cuento y la expresión oral en modalidad de enseñanza semipresencial en niños de la Institución Educativa Inicial N° 258 Gotitas de amor, Nauta 2022 - Pereyra Sandoval, Bertha Luz (2023)
The purpose of this study is to relate the Story and Oral Expression in blended learning modality in children of the Initial Educational Institution No. 258 Gotitas de Amor - Nauta 2022. For this study, 50 preschoolers of initial level were chosen as the sample size. The research is cross-sectional in nature and employs a field design that is relational to other studies. Data was collected through the use of observation, which was then used as a data collection tool. Prior to data collection, it was validated through the opinion of experts between the story and the oral expression in the modality of blended learning in children of the Initial Educational Institution No. 258 "Drops of Love", Nauta. In this reason it is validated with the correlation coefficient according to the Spearman's Rho coefficient value is (rs=-0.061*; Sig. < 0.05). the relationship is low, "There is no between the story and oral expression in blended learning modality in children of the Initial Educational Institution No. 258 Gotitas de amor Nauta 2022"